Des tilleuls mutilés aux lacrimae rerum: Le Virgile de la Vie de Henry Brulard - Pataki, Elvira (Verbum – Analecta Neolatina, 2015)
The aim of the article is to examine the ambiguous attitude of Stendhal towards classical antiquity, starting from some allusions to Latin literature in his autobiographical work Vie de Henry Brulard. As a first step, the analysis, based on an interdisciplinary approach, would give a panoramic view of the classical authors, who are considered by Stendhal as the representatives of a permanent romanticism, and consequently have a serious impact on the development of his literary taste and aesthetic canon. The paper focuses on three allusions to Virgil, stressing their philological, aesthetic and psychological issues. The three passages as a whole – a problematic pseudo-citation Nunc erubescit ver, inserted into an odd biographical context and surrounded by an allusion to the Georgics and by a famous verse of the Aeneid – seems to form a remarkable narrative triptych which is marked both by vulgar humiliation and subtility, illustrating the turbulent relationship between the novelist and his Classics.